A Study of audit clients characteristics and the determination of audit fees in an Automated Accounting System Environment - Akinola, Amos; Adejuwon, Joshua Adewale (The Journal of Accounting and Management, 2022)
The aim of this study was to examine various characteristics of clients that should be considered in the determination of audit fees in an automated accounting system (AAS). The study was built on those characteristics that had been examined over the years but in a manual accounting system environment which results may not be realistic until proven otherwise for an AAS environment. The study adopted a survey research design and relied on primary data sourced through questionnaire on four likert’s scale and five hundred and fifty one questionnaire were distributed to chartered accountants in private practice in South-West zone, Nigeria, out of which three hundred and eighty nine were filled and returned but three hundred and sixty two were considered valid. The questionnaire were descriptively analysed with percentage, mean and standard deviation and the results suggest that clients’ complexity in an automated accounting system environment will influence determination of audit fees. Also, clients’ size will affect the determination of audit fees and that clients’ profitability will influence the determination of audit fees in an automated accounting system environment. The grand mean secured from the respondents on each of clients’ characteristic are 2.58, 2.77 and 3.12 respectively and are all within agreed classification. Study concludes that determination of auditors fees in an automated accounting system will be influenced by these characteristics. The study therefore suggests that audit clients should be prepared to factor these into negotiation for a fee for audit service. Similarly, external auditors should build their fees negotiation around these clients’ characteristics.